Cost Control Factors Influencing Operational Performance In The Government Human Settlement Unit In South Africa - JWARA, Msawenkosi Cedric; NZUZA, Zwelihle Wiseman; MARIMUTHU , Ferina (Journal of Ecohumanism, 2025)
Purpose: To explore cost control factors influencing operational performance in the government human settlement unit in South Africa. Operational performance in this study was measured through the prism of administrative and human settlement functions. Employing a quantitative approach, this study employed cross-sectional design, utilizing census sampling to gather data from a cohort comprising 44 staff members hailing from relevant units. Method: The used Panel-corrected standard error (PCSEs) regression model at a confidence level below 0.05. Results: Internal factors (staff skills, leadership skills, and organizational culture) and an external factor (market environment) significantly affect operational performance (Human settlement function) at a statistical significance below 0.05. Originality/relevance: A comprehensive analysis of both internal and external cost control factors to identify areas for improvement on operational performance and enhance service delivery to the community.